MODEL PEMBELAJARAN PESANTREN DALAM MEMBINA MORALITAS SANTRI DI PONDOK PESANTREN SABILUL HASANAH BANYUASIN - Ema Dwi Fitriyani; Abu Mansur; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Morality children in Indonesia have experienced morality degradation which is very concering starting from, drug abuse, student brawls, and criminal acts. The cause of the decline in child morality is deviant associations, the entry of westernized culture, resulting in a negative state. There fore we need an educational instution that can foster children’s morality, one of which is the pesantren eductional instution. This study aims to determine what learning models are carried out by pesantren in fostering the morality of students. And to find out what factor support and hinder the pesantren of student’s morality In pesantren Sabilul Hasanah.. This research includes qualitative field research, using a case study approach to perfrom deep ekspolasi and research informants using purposive sampling. Data collection techniques using, observation, interviews, and documentation while the data analysis techniques uses data reduction, data display and verification. The results of this study indicate that the pesantren learning model in fostering the morality of students in pondok pesantren Sabilul Hasanah Banyuasin getting very good attention from the pesantren. This is shown from the rules which are applied by the pesantren which is arranged through manners and laws pesantren Sabilul Hasanah Banyuasin. Supporting factors in fostering student morality seen from the pesantren environment and ways of parenting the chaplain. Inhibiting factors in discussing the morality of students consisting of internal factor that come from within the student and external factor originating from the family and community evironment.